Perception of Body Image Among Sportspersons - Szucs, Robert SÃ¡ndor; Polya, Eva; Szakaly, ZoltÃ¡n (European Scientific Journal, ESJ, 2020)
Relationship between body and self-image is a well-known and frequently investigated process. Most especially among athletes, this area has been accentuated till the last decades in the literature. This paper focuses on investigating the attitude of people engaged in sports on a regular basis by concentrating primarily on the perception of their body image, the type and form of sport activities, and the consumption habits of food supplements. After a short literature review, the results of the primary research are introduced. People who took part in the research are engaged in sports on a regular basis, and they do sport activities at least once a week on their own free will. Paper Assisted Personal Interviews (PAPI) was used, primarily concentrating on the attitudes of the respondents. During the research, the following conclusions were made: subjectively perceived â€œnormalâ€ body shape category moving higher and the social judgement of overweight became more and more accepted. Owing to the ideal body shape presented by the consumer society, slimmer people want to become thicker while people with a stronger shape want to become leaner. Hence a social problem come into being that only exist in the athleteâ€™s mind. This phenomenon can fundamentally base the headway of food supplements since the producers offer solutions to all segmentsâ€™ real or putative problems. The mostly unreal body ideals boost the dissatisfaction of people towards their own bodies. Producers and distributors of food supplements not only emphasize and draw their customersâ€™ attention to the imperfection of their shape, but they also offer a solution to their real or putative problems. The more the consumer is hesitating, the more favourable it is for the producer as the possibility of purchasing is greater.